Enabling End-host Network Functions - Ballani, Hitesh; Costa, Paolo; Gkantsidis, Christos; Grosvenor, Matthew P.; Karagiannis, Thomas; Koromilas, Lazaros; O'Shea, Greg (The ACM SIGCOMM Conference on Data Communication (SIGCOMM), 2015)
Many network functions executed in modern datacenters, e.g., load balancing, application-level QoS, and congestion control, exhibit three common properties at the data plane: they need to access and modify state, to perform computations, and to access application semantics — this is critical since many network functions are best expressed in terms of application-level messages. In this paper, we argue that the end hosts are a natural enforcement point for these functions and we present Eden, an architecture for implementing network functions at end hosts with minimal network support. Eden comprises three components, a centralized controller, an enclave at each end host, and Eden-compliant applications called stages. To implement network functions, the controller configures stages to classify their data into messages and the enclaves to apply action functions based on a packet's class. Our Eden prototype includes enclaves implemented both in the OS kernel and on programmable NICs. Through case studies, we show how application-level classification and the ability to run actual programs on the data-path allows Eden to efficiently support a broad range of network functions at the network's edge.